Racial/Ethnic Disparity Trends in Children's Mental Health Care Access and Expenditures from 2002 to 2007. (20th June 2012) - Cook, Benjamin Lê; Barry, Colleen L.; Busch, Susan H.
<x xml:space="preserve">Abstract</x> Objective To examine trends in disparities in children's mental health care. Data 2002–2007 Medical Expenditure Panel Survey. Study Design We used the Institute of Medicine (IOM) definition of health care disparities and estimated two‐part expenditure models to examine disparity trends in any mental health care use, any outpatient care, and psychotropic drug use, as well as expenditures in these three categories, conditional on use. We used 2‐year longitudinal panel data to determine disparities in care initiation among children with unmet need. Principal Findings Assessing trends over time between 2002 and 2007, we identified that disparities persist for blacks and Latinos in receipt of any mental health care, any outpatient care, and any psychotropic drug use. Among those with positive mental health care expenditures, Latino–white disparities in overall mental health care expenditures increased over time. Among children with unmet need, significant disparities in initiation of an episode of mental health care were found, with whites approximately twice as likely as blacks and Latinos to initiate care. Conclusions Disparities in children's mental health care use are persistent and driven by disparities in initiation, suggesting policies to improve detection or increase initial access to care may be critical to reducing disparities.